Lower Tibial Tunnel Placement in Isolated Posterior Cruciate Ligament Reconstruction: Clinical Outcomes and Quantitative Radiological Analysis of the Killer Turn. Issue 8 (18th August 2020) - Lin, Yipeng; Huang, Zeyuan; Zhang, Kaibo; Pan, Xuelin; Huang, Xihao; Li, Jian; Li, Qi
Background: The "killer turn" effect after posterior cruciate ligament (PCL) reconstruction is a problem that can lead to graft laxity or failure. Solutions for this situation are currently lacking. Purpose: To evaluate the clinical outcomes of a modified procedure for PCL reconstruction and quantify the killer turn using 3-dimensional (3D) computed tomography (CT). Study design: Case series; Level of evidence, 4. Methods: A total of 15 patients underwent modified PCL reconstruction with the tibial aperture below the center of the PCL footprint. Next, 2 virtual tibial tunnels with anatomic and proximal tibial apertures were created on 3D CT. All patients were assessed according to the Lysholm score, International Knee Documentation Committee (IKDC) Subjective Knee Evaluation Form, Tegner score, side-to-side difference (SSD) in tibial posterior translation using stress radiography, and 3D gait analysis. Results: The modified tibial tunnel showed 2 significantly gentler turns (superior, 109.87° ± 10.12°; inferior, 151.25° ± 9.07°) compared with those reconstructed with anatomic (91.33° ± 7.28°; P < .001 for both comparisons) and proximal (99° ± 7.92°; P = .023 and P < .001, respectively) tibial apertures. The distance from the footprint to the tibial aperture was 16.49 ± 3.73 mm. All patient-reported outcome scores (mean ± SD) improved from pre- to postoperatively: Lysholm score, from 46.4 ± 18.87 to 83.47 ± 10.54 ( P < .001); Tegner score, from 2.47 ± 1.85 to 6.07 ± 1.58 ( P < .001); IKDC sports activities score, from 19 ± 9.90 to 33.07 ± 5.35 ( P < .001); and IKDC knee symptoms score, from 17.87 ± 6.31 to 25.67 ± 3.66 ( P < .001). The mean SSD improved from 9.15 ± 2.27 mm preoperatively to 4.20 ± 2.31 mm postoperatively ( P < .001). The reconstructed knee showed significantly more adduction (by 1.642°), less flexion (by 1.285°), and more lateral translation (by 0.279 mm) than that of the intact knee ( P < .001 for all). Conclusion: Lowering the tibial aperture during PCL reconstruction reduced the killer turn, and the clinical outcomes remained satisfactory. However, SSD and clinical outcomes were similar to those of previously described techniques using an anatomic tibial tunnel.